Class III Polyphosphate Kinase 2 Enzymes Catalyze the Pyrophosphorylation of Adenosine‐5′‐Monophosphate. (22nd August 2019) - Ogawa, Marin; Uyeda, Atsuko; Harada, Kazuo; Sato, Yu; Kato, Yasuhiko; Watanabe, Hajime; Honda, Kohsuke; Matsuura, Tomoaki
Abstract: Polyphosphate kinase 2 (PPK2) transfer phosphate from inorganic polyphosphate to nucleotides. According to their activity, PPK2 enzymes are classified into three groups. Among them, class III enzymes catalyze both the phosphorylation of nucleotide mono‐ to diphosphates and di‐ to triphosphates by using polyphosphate, which is a very inexpensive substrate. Therefore, class III enzymes are very attractive for use in biotechnological applications. Despite several studies on class III enzymes, a detailed mechanism of how phosphate is transferred from the polyphosphate to the nucleotide remains to be elucidated. Herein, it is reported that PPK2 class III enzymes from two different bacterial species catalyze the phosphorylation of adenosine mono‐ (AMP) into triphosphate (ATP) not only through step‐by‐step phosphorylation, but also by pyrophosphorylation. These are the first PPK2 enzymes that have been shown to possess polyphosphate‐dependent pyrophosphorylation activity. Abstract : Tracing transfers : Polyphosphate kinase 2 (PPK2) transfer phosphate from inorganic polyphosphate to nucleotides. Among them, class III PPK2 enzymes can transfer pyrophosphate from polyphosphate to convert adenosine mono‐ (AMP) into triphosphate (ATP). The reaction mechanisms of these enzymes from two different bacterial species are investigated.